Корпоративна культура польських та українських підприємств в умовах цифровізації: порівняльний аналіз - Чернух, Д.В. (Вісник економічної науки України, 2023)
Цифрова трансформація є одним із найважливіших трендів сучасного бізнесу. Вона вимагає від підприємств змін у їхніх бізнес-процесах, моделях управління та корпоративній культурі. Умови цифровізації сьогодні створюють нові виклики для організаційної культури. У статті досліджено формування корпоративної культури польських та українських підприємствах в умовах цифровізації, що є актуальним завданням в контексті сучасних тенденцій у глобальному бізнесі. Для досягнення поставленої мети були використані різні методи дослідження, такі як порівняння, спостереження, системного підходу, структурного аналізу, факторного аналізу, методу синтезу, формалізації, структурно-логічного узагальнення. Метою наукової роботи є проаналізувати особливості корпоративної культури польських та українських підприємств в умовах цифрової трансформації. Зокрема у науковій роботі досліджено: характер відносин між працівниками та керівниками, стиль управління, сприйняття ризиків, відкритість до нововведень, важливість командної роботи та особистої ефективності. Встановлено ключові відмінності корпоративної культури польських та українських транспортно-логістичних підприємств. Виявлено переваги та недоліки організаційної культури компаній. Досліджено та узагальнено основні чинники які впливають на корпоративну культуру польських та українських підприємств. Встановлено та виокремлено проблеми українського бізнесу в умовах війни та основні причини міграції компаній закордон. Digital transformation is one of the most important trends in modern business. It requires enterprises to change their business processes, management models, and corporate culture. The conditions of digitalization today create new challenges for organizational culture. The article investigates the formation of corporate culture in Polish and Ukrainian enterprises in the context of digitalization, which is an urgent task in the context of modern trends in global business. To achieve the set goal, a variety of research methods were used, such as comparison, observation, systems approach, structural analysis, factor analysis, synthesis method, formalization, and structural-logical generalization. The purpose of the research is to analyze the features of corporate culture of Polish and Ukrainian enterprises in the context of digital transformation. In particular, the research investigated the following: the nature of relationships between employees and managers, management style, risk perception, openness to innovation, the importance of teamwork and personal effectiveness. Key differences in the corporate culture of Polish and Ukrainian transportation and logistics enterprises were established. The advantages and disadvantages of the organizational culture of companies were identified. The main factors affecting the corporate culture of Polish and Ukrainian enterprises have been investigated and summarized. The problems of Ukrainian business in the context of war and the main reasons for the migration of companies abroad have been established and highlighted. Key recommendations for Polish and Ukrainian companies to successfully adapt to digital transformation: invest in digital technologies and infrastructure; develop a digital strategy; empower employees to embrace change; measure and track progress.This study showed that digitalization has both positive and negative impacts on corporate culture. Specifically, among the positive factors, it is worth highlighting the increase in transparency and accessibility of information, the improvement of communication and interaction, and the development of innovation and creativity. Among the negative ones, the increase in stress and burnout, the decrease in personal communication, and the increase in staff turnover. During the study, it was found that digital transformation has a significant impact on corporate culture. It requires companies to adapt to new technologies, changes in ways of working and interacting with customers and employees. Therefore, Polish and Ukrainian companies need to follow these recommendations to improve corporate culture: ensure transparency and accessibility of information;  improve communication and collaboration; promote innovation and creativity; provide employee support; provide employee support.